Seed vigor classification using analysis of mean radicle emergence time and single counts of radicle emergence in rice (Oryza sativa L.) and mung bean (Vigna radiata (L.) Wilczek) - Onwimol, Damrongvudhi; Chanmprasert, Wanchai; Changsee, Petchlada; Rongsangchaichareon, Thunyapuk (Agriculture and Natural Resources, 2016)
The radicle emergence (RE) test for seed vigor classification is an ingenious protocol that will lead to a fast and reliable automated procedure for verifying seed quality using image analysis. Nevertheless, the success of this protocol has never been described in rice and mung bean that are global staple foods. This experiment analyzed the correlation between RE (2 mm in length) and normal seedlings (NS) during a germination test of rice and mung bean. In total, 12 samples using four cultivars of each species were obtained from different locations and production years. In addition to the germination test, an accelerated ageing (AA) test and an electrical conductivity (EC) test were analyzed. The results revealed that the pattern of the cumulative germination curve of RE and NS coincided but the curve for NS was longer than for RE (p ≤ 0.05). There was no significant difference in the variance of the germination time between RE and NS of rice but there was a significant difference for mung bean. The vigor levels of the rice seed classified by single counts of RE at 110 h after set to germinate (HASG) conformed to the result of single counts of NS at 200 HASG and the result of the AA test. However, these classifications disagreed with the result derived from the EC test. In contrast, the mung bean vigor level classified by single counts of RE, NS, the AA test and the EC test did not relate well with each other. In conclusion, it is possible to develop the automated procedure for verifying rice seed quality using image analysis via a single count of RE.